The drone debate a primer on the U.S. use of unmanned aircraft outside conventional battlefields - Plaw, Avery; Fricker, Matthew S.; Colon, Carlos R. (Rowman & Littlefield Publishers, 2016)
The Drone Debate offers a thorough investigation of the where, why, how, and when of the U.S. use of unmanned aerial vehicles. Beginning with a historical overview of the use of drones in warfare, it then addresses whether targeted killing operations are strategically wise, whether they are permissible under international law, and the related ethical issues.